Analisis Perbandingan Kinerja Cryptocurrency Bitcoin, Saham, dan Emas sebagai Alternatif Investasi - Christopher Lumbantobing; Isfenti Sadalia (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: This research aimed to find out and analyze the comparison of Bitcoin, stocks, and gold performances. Research methodology: The analytical method used in this research is a comparative method by using secondary data. Microsoft Excel program was used to calculate the formula of each variable. Then, the data were processed statistically by using the SPSS application, the Kurskall-Wallis Test. Results: This study indicates that there is no significant difference between Bitcoin, LQ45 stocks, and gold when measured from return and Jensen’s performance measure. Then, there are significant differences between Bitcoin, LQ45 stocks, and gold when measured from risk, Sharpe performance’s measure, and Treynor performance’s measure Limitations: The data used in this research were only from April 2013 – October 2019. Contribution: This research contributes to investors and anyone who wants to invest.